The relatively young and metal-poor Galactic open cluster NGC 2194 - Piatti, Andres Eduardo (2003)
We present CCD VIKC photometry down to V≈ 21 mag in the field of the rich open cluster NGC 2194, which is projected towards the Galactic anticentre direction. We measured V magnitudes and V−I colours for a total of 2515 stars in a field of 13.6 × 13.6 arcmin2. These data are supplemented with CCD photometry in the C, M and T1 filters of the Washington system and photoelectric CMT1T2 photometry of 20 red giant candidates. Based on the best fits of isochrones computed by the Geneva and Padova groups to the (V, V−I) colour–magnitude diagram, we derive a colour excess E(V−I) = 0.75, a cluster distance of 3.2 kpc and an age of 400 Myr. Five independent Washington abundance indices yield a mean cluster metallicity of [Fe/H]=−0.27 ± 0.06, which is compatible with the existence of both a radial and Z gradient in the Galactic disc. NGC 2194 is a relatively young open cluster, whose deficiency in metal content can be accounted for by the fact that it was born not only far from the Galactic centre in the outer disc, but also at a relatively high Z value.